Assessing Student Learning in Africa - Kellaghan, Thomas; Greaney, Vincent (Washington, DC: World Bank, 2013)
This paper reviews what has happened in the field of assessment since then. It deals with public examinations, but differs from the 1992 report in that, other than in regard to a few minor details, no new data were specifically collected for it. The paper revisits many of the issues that were raised in the earlier report, particularly in relation to the role that assessment can play in improving the quality of students' learning. It also differs from the earlier report in that its consideration of assessment is not limited to public examinations. The World Declaration on Education for All in Jomtien in 1990 not only gave fresh impetus to issues relating to assessment, but also necessitated the introduction of a new form of assessment-system assessment, or national assessment-to determine if children were acquiring the useful knowledge, reasoning ability, skills, and values that schools promised to deliver. National assessment is the second major area of assessment addressed in this paper. International assessments, which share many procedural features with national assessment, are also considered. The fourth type of assessment addressed in the paper is classroom assessment.